Space‐Confined Synthesis of 2D All‐Inorganic CsPbI3 Perovskite Nanosheets for Multiphoton‐Pumped Lasing. Issue 22 (3rd October 2018) - Zheng, Zhi; Wang, Xiaoxia; Shen, Yanwei; Luo, Ziyu; Li, Leigang; Gan, Lin; Ma, Ying; Li, Huiqiao; Pan, Anlian; Zhai, Tianyou
Abstract: With multiphoton‐pumped lasing, 2D all‐inorganic CsPbI3 perovskite nanoplates demonstrate a wide range of applications which results from its high crystalline quality and a nearly perfect naturally formed whispering gallery mode cavity. However, there still remains a difficulty in controllable synthesizing 2D CsPbI3 nanosheets with high crystalline quality. In this work, high‐quality 2D CsPbI3 perovskite nanosheets have been synthesized successfully with controllable morphology through space‐confined vapor‐phase epitaxial growth. More importantly, the morphology and crystalline quality of CsPbI3 perovskite nanosheets could be easily tuned by adjusting the diffusion and growth process achieved by adjusting the space‐confined distance and growth temperature. The typical square‐like CsPbI3 perovskite nanosheets can be as thin as 6.0 nm with a lateral size of 10.0 µm. The photoluminescence emission properties show a distinct dependence on thickness of these as‐grown CsPbI3 perovskite nanosheets. In addition, the as‐fabricated CsPbI3 perovskite nanosheets demonstrate one‐photon and two‐photon excitation‐pumped lasing with low‐threshold and high‐quality factor. The excellent multiphoton‐pumped lasing properties of the CsPbI3 perovskite nanosheets are attributed to their high crystalline quality, implying great promise for future applications in high‐performance optoelectronics. Abstract : 2D all inorganic CsPbI3 perovskite nanosheets demonstrate potential application in multiphoton‐pumped lasing . Herein, a space‐confined strategy is adopted to controllable synthesis of square CsPbI3 nanosheet with high crystalline quality. Moreover, the impact of diffusion and growth reaction on the growth dynamics is systematically investigated. The CsPbI3 perovskite nanosheet exhibits low threshold lasing behavior both at one‐ and two‐photon‐pumped excitation.